THE SOCIAL POSITION AND TYPOLOGY OF MADURESE WOMEN IN MADURA FOLKTALES - Harits, Imron Wakhid (Balai Bahasa Jawa Timur, 2011)
Abstract: The aim of this study is to observe the woman position in the social life in Madura and observes the typology of Madurese women on three Madura folktales, i.e. Aer Mata Ebu, The Origin of Madura, and Aryo Menak and His Wife. To analyze the social position and typology of women, this study uses the Cixous?s theory of feminism. Qualitative method with ethnography aprroach is used to do this research. These three folktales have similarities, because all of these three folktales tell about the struggle, tough, firmness, sincere of Madurese women. Thus, by analyzing these folktales, the women social position in Madura can be observed. The women are considered as the holy creature that must be appreciated. From the analysis, several typologies of Madurese woman reflected in the folktales can also be identified, i.e. sincere, firmness, tough, religious, and sufism. Abstrak: Makalah ini bertujuan mengobservasi posisi wanita dalam kehidupan sosial masyarakat Madura dan meneliti tipologi wanita?wanita Madura pada tiga cerita rakyat Madura, yaitu Aer Mata Ebu, Asal?Usul Pulau Madura, dan Aryo Menak dan Istrinya. Untuk menganalisis posisi sosial dan tipologi wanita digunakan teori feminisnya Cixous. Untuk mengungkap aspek-aspek sosial yang mempengaruhi cerita rakyat tersebut digunakan metode kualitatif dengan pendekatan etnografi. Ketiga cerita rakyat ini memiliki banyak kesamaan karena ketiganya menggambarkan perjuangan, keuletan, ketabahan, dan ketulusan wanita? wanita Madura. Dengan demikian, dengan menganalisis cerita?cerita rakyat ini, dapat diamati posisi sosial wanita?wanita Madura. Para wanita diposisikan sebagai makhluk suci dan terhormat. Berdasarkan analisis tersebut juga ditemukan tipologi wanita-wanita Madura yang tercermin dalam cerita rakyat tersebut, yaitu tulus, tabah, ulet, agamis, dan sufi. Kata-Kata Kunci: feminisme, cerita?cerita rakyat Madura, tipologi